Análisis de costos de sigatoka negra en el cultivo de banano - Cherrez Molina, Manuel José (2010)
The development of this project took place in the Zone of Guayas Province called Piedrero, the purpose of it is the implementation of cost analysis of the control of Black Sigatoka, investigating both the method of the Committee of Action for the Resistance Fungicides "Method FRAC" which meets in an appropriate way the proposed guidelines thus preserving the fungicide molecules and providing an appropriate control for the plantation, the Traditional Method takes control in an empirically more economic way without an action plan. For this analysis it was necessary to compile the information and the respective analysis of the productions and the number of fungicide applications. The methodology used to study them is the analysis of variance. Concluding that the FRAC is the optimal method for inspecting the health of Black Sigatoka in banana cultivation.